A proposal to teach medical students how to use interpreters - Kyle Thomas; Nicole Jacobs; Alexandra Lopez Vera (Springer, 2024)
Abstract Introduction Medical interpreters are crucial to ensure fair and high-quality healthcare for patients with limited English proficiency (LEP). Despite the need to use high-quality medical interpreters to communicate with LEP patients, medical schools often do not adequately educate their students on how to work with interpreters. Aims This study seeks to investigate the efficacy of using peer-assisted learning to teach medical students how to properly use medical interpreters. Moreover, the study strives to elucidate if an interactive peer-led model can be an effective teaching modality to train medical students about the basics of using medical interpreters. Methods A pre- and post-training design was utilized to investigate the efficacy of peer-assisted learning in teaching medical students how to use interpreters. Second year medical students led a two-part workshop consisting of the following: (1) a didactic training session and (2) a practical session where learners interacted with Spanish-speaking standardized patients through an interpreter. Pre-training and post-training responses to survey questions were analyzed to determine changes in student comfort, confidence, and knowledge of best practices when using a medical interpreter. Results There was a statistically significant increase in comfort and confidence with using interpreters after receiving peer-assisted training. Conclusions A peer-led didactic training followed by an interactive training session can increase student comfort and confidence with using medical interpreters in clinical settings. Peer-assisted-learning may be an effective way to teach some of the best practices of using medical interpreters.